Kajian Partisipasi Siswa dalam Aspek Kegiatan Lingkungan Hidup pada Sekolah Adiwiyata Nasional di SMP Negeri 1 Jatilawang Kabupaten Banyumas - Lenny Susanti (Pascasarjana Universitas Jenderal Soedirman, 2021)
The success or failure of the Adiwiyata program implementation will be primarily determined by the level of student participation as learning subjects in schools. For student care and participation to be well-formed following Adiwiyata goals, school programs that support environmental education are needed through extracurricular, extracurricular activities, and school development programs. This study aims to find whether there is a relationship between student ecological concern and the type of Adiwiyata activity with the level of student participation either partially or simultaneously in the Adiwiyata program at SMP Negeri 1 Jatilawang. The method used in this research is a survey method using a questionnaire as the main instrument for collecting data. The population in this study was 809 students of SMP Negeri 1 Jatilawang Banyumas, with a total sample of 89 students. The bivariate analysis uses Kendall's Tau Correlation (τ) or Tau from Kendall, while the multivariate use Kendall's W concordat coefficient. The results show that the positive correlation coefficient is 0.757; this indicates that the student's environmental awareness variable (X1) has a strong relationship.